Patrick Geddes – not only a town planner but a poet too - Biger, Gideon (Studia z Geografii Politycznej i Historycznej, 2013)
Sir Patrick Geddes, one of the fathers of modern town planning, worked as a town planner in Palestine during the 1920’s. He was motivated mainly by his Zionist feeling which can be seen in an unknown poem written by him concerning his attitude toward his work. This poem, which has never been published, presenting his admiration for the old-new Zionist ideology and the way that gifted man bonded together his knowledge of the Bible, his Scottish roots and his work into a poem, found in his unpublished private papers.